The verification of the modernization of the real estate cadastre in the context of the quality of cadastral data – case study - Mika, Monika (International Conference “Environmental Engineering”, 2017)
The aim of the modernization is to improve the quality of the collected data. That is necessary especially in those areas where cadastral maps are used in the scale of 1:2880. The most satisfactory results in the process of modernization are obtained on the basis of geodetic field measurements. The aim of the paper is to verify the work related to real estate cadastre modernization in the context of the quality of the cadastral data collected in 1999–2001. This paper presents the results of surveying, which aim was to check whether the data contained in the register of land are a reflection of the facts boundaries and surface parcels. In the analyzes the materials of selected areas from state resources were used. The verification of graphic materials (maps) and descriptive (areas of plots) obtained from the District Office carried out in this paper showed a satisfactory level of data compliance. Factual status on the ground, in most cases, corresponds to the existing in extracts from the land registry, created on the basis of the land and buildings registry modernization in 1999–2001. These data correspond to the areas calculated from the results of the 2016 direct measurements.